Immobilization of Vibrio cholerae S1 (NAG) L-Glutaminase on Different Supports (Baghdad Science Journal, 2010)
Sixteen Vibrio isolates producing L-glutaminase were obtained from clinical and water samples , one isolate was selected according to its’ highest enzyme productivity , it was identified as Vibrio cholerae (NAG) and coded as V. cholerae S1.The bacteria was cultured in a liquid medium (containing L-glutamine) , L-glutaminase was extracted from the cells by ultrasonication , the enzyme was precipitated by 30 % saturation of ammonium sulphate , dialyzed and immobilized by adsorption on different supports including Sephadex G-100 , cellulose powder , starch , silica gel , glass beads and charcoal.Sephadex G-100 retained most of enzyme activity (90 %) followed by starch (78 %) , then silica gel and cellulose powder (71 %) while glass beads and charcoal retained 58 % only.The immobilized enzyme was subjected to different temperatures and pHs. The results showed that the immobilized enzyme is more stable than the free enzyme in different temperatures and pHs. Silica gel was the best matrix for protecting L-glutaminase against heat , it retained 52 and 22 % of the original activity after 2 hrs of incubation at 50 and 60 ۫c respectively while the free enzyme retained 30 and 10 % at the same conditions.The immobilized enzyme was more stable at pH 7 than at pH 4 or 10 . the enzyme adsorbed on Sephadex G-100 retained the maximum activity (98 %) at pH 7 for 2 hrs , while it was 73 % for the free enzyme.The immobilized L-glutaminase of V. cholerae S1 (with Sephadex G-100) was stored at 4 ۫c for 30 days , the remaining activity was 35 % , while it was 18 % for the free enzyme.It can be concluded from these results that V. cholerae S1 L-glutaminase can be immobilized on different inert materials, Sephadex G-100 is more suitable in this project , Silica gel can protect the enzyme against heat. In general the immobilized enzyme is more stable at different temperatures , pH and time than the free enzyme.